Antiulcer Activity of Clerodendrum Serratum Extract on Albino Rats - Nayak, Jyoti; Pandey, Adityanath; Mishra, Jai Narayan (Journal of Neonatal Surgery, 2025)
Clerodendrum serratum (Verbenaceae) is an important medicinal plant growing in the tropical and warm temperate regions like Africa, Southern Asia; Malaysia and distributed throughout in forests of India and Sri Lanka. It is traditionally valued and reported for treating pain, inflammation, rheumatism, respiratory disorders, fever and malarial fever in India with a long history.Ethnomedicinal uses C. serratum (Bharangi) is widely used in indigenous systems of medicine for the treatment of respiratory disease, especially asthma, and several other diseases in a crude combination with several other drugs According to Aryabhishek it is useful in cough, swelling, breathlessness, wound, fever, rheumatism, tuberculosis etc. The Ayurvedic Pharmacopoeia of India indicated the use of the dried roots for cough, bronchitis, dyspnea, chest diseases and sinusitis. Pharmacognostic evaluation established the macroscopic and microscopic parameters for the identification of whole plant and its powder. Physicochemical parameters were also set forth while quantitative phytochemical analysis showed that the ethyl acetate fraction had the highest quantity of phenols, flavonoids, and tannins. The present study was carried by aspirin plus pylorus ligation induced ulcer models in albino rats. The antiulcer activity of ethanolic extract of Clerodendrum Serratum (EOCS) and ethyl acetate extract of ClerodendrumSerratum (EACS) were compared with standard drugs (Ranitidine). In pyloric ligation induced ulcer model, the studied parameters were gastric volume, pH, total acidity, free acidity, and ulcer index.In aspirin pyloric ligation model the volume of gastric content, total/free acidity and pepsin activity was significantly decreased and pH of the gastric juice was significantly increased at in EOCS treated groups as compared to control group. All the doses of EOCS showed dose dependent antiulcer effect as well as significant (p<0.05) reduction in the ulcer index as compared to control group in all the experimental models.The results of the study indicate that the Ethanol extract of Clerodendrum serratum have better potential against ulcer.